Shaping the future of Ethereum: exploring energy consumption in Proof-of-Work and Proof-of-Stake consensus - Asif, Rameez; Hassan, Syed Raheel (Frontiers in Blockchain, 2023)
Ethereum (ETH) is a popular Layer-1 blockchain platform that has been used to create decentralized applications (dApps) and smart contracts. Ethereum 2.0, or Serenity, is a significant update to the network that intends to address numerous issues with scalability, security, and energy efficiency. The Proof-of-Stake (PoS) consensus method will replace the Proof-of-Work (PoW) mechanism, which is one of the major new features of Ethereum 2.0. Given that PoS doesn't require miners to do intensive mathematical calculations in order to validate transactions, it has the potential to be more energy-efficient than PoW. Additionally, this Ethereum upgrade will also be more secure due to the introduction of a new mechanism called "Casper" that will ensure that validators are always in agreement on the state of the blockchain. The paper begins by discussing the current issues facing Ethereum, including the limitations of the Proof of Work (PoW) consensus mechanism and the need for more efficient and scalable solutions. In this study, we peered at the major changes introduced by Ethereum 2.0, such as the new consensus method (Proof-of-Stake) and the addition of shard chains (Ethereum 2.0), as well as the associated development timelines, benefits and the community criticism on this upgrade.